How Does Banking Innovation Impact Banking Stability in Indonesia? The Moderating Role of Gender Diversity - Kartiko, Nafis Dwi (The International Journal of Financial Systems, 2024)
This study aims to examine the impact of banking innovation on banking stability in Indonesia. Using financial data from 46 banks listed on the Indonesia Stock Exchange from 2004 to 2022 with 637 observations, this study applies the Ordinary Least Squares (OLS) method for its analysis. The results of this study show that banking innovation exerts a significant positive influence on banking stability in Indonesia. However, a surprising finding emerges from the moderation of gender diversity which turns out to have a negative effect on the relationship between banking innovation and banking stability, contrary to the literature that often shows a positive effect of gender diversity on firm performance. Additional analysis suggests that despite innovations, SOEs with strict structures and regulations may not be able to fully capitalise on the efficacy of such innovations due to bureaucratic barriers and strict government policies. In contrast, non-SOE firms are more agile and able to implement innovations with higher effectiveness, which contributes to their financial stability. The study also analyses various financial quadrants, showing that the effect of innovation on banking stability varies based on asset characteristics and firm age.